Lossless Image Authentication Algorithm Based on Three-Compa Image Basic Blocks - Xiangyang Li (2013 Eighth International Conference on P2P, Parallel, Grid, Cloud and Internet Computing, 2013)
As the existing block-wise loss less image authentication algorithms sacrifice the precision of locating distortions, a new loss less image authentication algorithm based on three-compa image basic blocks is proposed. The algorithm trisects the original image recursively in order to get basic blocks. When the watermark can't be embedded into the authentication block, the algorithm tries to merge only one basic block into current authentication block. As a result, each authentication block's size is expanded at a minimum level. Moreover, in order to prevent vector quantization attack, a digital signature algorithm is taken and signature is repeatedly embedded into the authentication block via a loss less watermarking algorithm. Theoretical analysis and experimental results demonstrate that the algorithm is more accurate than the algorithm based on adaptive combinations of image basic blocks.